2017
DOI: 10.1038/s41598-017-11264-3
|View full text |Cite
|
Sign up to set email alerts
|

Alpha subunit-dependent glycine receptor clustering and regulation of synaptic receptor numbers

Abstract: Accumulation of glycine receptors at synapses requires the interaction between the beta subunit of the receptor and the scaffold protein gephyrin. Here, we questioned whether different alpha subunits could modulate the receptors’ diffusion and propensity to cluster at spinal cord synapses. Using quantitative photoactivated localisation microscopy we found that alpha-1 and alpha-3 containing glycine receptors display the same α3:β2 stoichiometry and gephyrin binding. Despite these similarities, alpha-3 containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(87 citation statements)
references
References 46 publications
6
80
1
Order By: Relevance
“…Using immunocytochemistry, previous work indicated that approximately half of lamina II neurons appear to co-express both subunits, and our data in the GAD-65 cell population are consistent with these results (Harvey et al, 2004). Recent work in cultured neurons indicates that IL-1β does not affect GlyRα3-containing receptors, although IL-1β potentiation of GlyRα1- containng receptors was not observed in this study (Patrizio et al, 2017).…”
Section: Discussioncontrasting
confidence: 83%
“…Using immunocytochemistry, previous work indicated that approximately half of lamina II neurons appear to co-express both subunits, and our data in the GAD-65 cell population are consistent with these results (Harvey et al, 2004). Recent work in cultured neurons indicates that IL-1β does not affect GlyRα3-containing receptors, although IL-1β potentiation of GlyRα1- containng receptors was not observed in this study (Patrizio et al, 2017).…”
Section: Discussioncontrasting
confidence: 83%
“…For instance, quantitative 3D-PALM analysis has revealed the gephyrin organization in inhibitory synapses in cultured spinal cord neurons: the ensuring calculations estimated the postsynaptic clusters of 40–500 gephyrin molecules, packed at a density of about 5000 molecules/μm 2 , whereas synapses in situ contained about three times as many molecules and were packed more densely (Specht et al, 2013 ). The same group recently used quantitative PALM to show that alpha-1 and alpha-3 containing glycine receptors display the same α 3 :β 2 stoichiometry and gephyrin binding (Patrizio et al, 2017 ). However, the authors found that alpha-1 containing receptors are more mobile and less densely packed (1100 molecules/μm 2 vs. 1500 molecules/μm 2 ; alpha-3 containing receptors) and that their number at synapses was reduced in response to interleukin 1β.…”
Section: Sr Imaging Of the Postsynaptic Sitementioning
confidence: 99%
“…The PSD has mostly been studied in glutamatergic neurons, where AMPA and NMDA ionotropic receptors are clustered, proximal to the pre-synaptic AZ sites (Boeckers, 2006;Chen et al, 2015;Tang et al, 2016;Scheefhals and MacGillavry, 2018). Ionotropic glycine receptor clustering was also reported in the membrane of the postsynaptic cell (Patrizio et al, 2017;Schaefer et al, 2018). Such clusters are found in motor neuronal membranes of the adult spinal cord, brain stem, and retina, and were shown to be essential for proper neuron hyperpolarization.…”
Section: Site-specific Clustering Of Ion Channels Affects Signal Genementioning
confidence: 99%
“…Such clusters are found in motor neuronal membranes of the adult spinal cord, brain stem, and retina, and were shown to be essential for proper neuron hyperpolarization. Impaired clustering of glycine receptors is associated with startle disease in mice (Patrizio et al, 2017;Schaefer et al, 2018). The clustering of different ion channels and receptors in proximity to other intracellular signaling and cytoskeletal structural proteins at the PSD is also essential for ensuring a robust response to neurotransmitter binding and for modulating the evoked synaptic potential, whether inhibitory or excitatory, of the post-synaptic cell membrane (Boeckers, 2006).…”
Section: Site-specific Clustering Of Ion Channels Affects Signal Genementioning
confidence: 99%